2018
DOI: 10.4187/respcare.06294
|View full text |Cite
|
Sign up to set email alerts
|

Humidification Performance of Passive and Active Humidification Devices Within a Spontaneously Breathing Tracheostomized Cohort

Abstract: BACKGROUND: Most heat-and-moisture exchangers (HMEs) for patients with tracheostomy and spontaneously breathing are small and have suction ports that allow some expiratory gas to escape, which loses water vapor held in the expired gas. Recently, a heated-and-humidified high-flow system for spontaneously breathing patients with tracheostomy was developed. Little is known, however, about the humidifying performance of HMEs or heated-and-humidified high-flow systems for spontaneous breathing patients with a trach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
5
3
Order By: Relevance
“…Some previous studies [13,16] indicated that C method usually gains better SpO 2 , while our results showed that the SpO 2 was lower and respiratory rate was higher in group B and C than group A, and no difference was observed between group B and C. The reason may be that, the cold air flow in group A cause the airway contraction and prevent the oxygen exchange, and the supplement of oxygen to the patients diminished the differences between group B and C.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Some previous studies [13,16] indicated that C method usually gains better SpO 2 , while our results showed that the SpO 2 was lower and respiratory rate was higher in group B and C than group A, and no difference was observed between group B and C. The reason may be that, the cold air flow in group A cause the airway contraction and prevent the oxygen exchange, and the supplement of oxygen to the patients diminished the differences between group B and C.…”
Section: Discussioncontrasting
confidence: 58%
“…1C). The temperature of the atomizer tank is adjusted to 39-41 °C, and the temperature before entering the patient's airway is 35.3 °C according to a previous report [13]. The pipeline is non-polluted and not replaced.…”
Section: Design and Patientsmentioning
confidence: 99%
“…HFNC did not affect decreased diaphragm contraction in this study ; however, it attenuated paradoxical diaphragm contraction. The work of breathing was decreased by HFNC in patients without diaphragm dysfunction as reported (10,11). The findings of this study suggest that HFNC may have the potential role to manage patients with paradoxical diaphragm contraction.…”
Section: Discussionmentioning
confidence: 55%
“…In subjects with tracheostomy who are spontaneously breathing, a heated-and-humidified high-flow system was reported to achieve higher absolute humidity than did an HME. 23 The active HME is increasingly being prescribed for long-term home mechanical ventilation as an alternative to heated humidifiers because it is lighter (42 g for the active HME vs 1.7 kg for the heated humidifier) and not cumbersome (the active HME consists of a mount catheter and a breathing filter connected to a booster vs several more components for the heated humidifier) and so it is able to facilitate the patient's movements. In addition to its opti-mum humidifying properties, which are particularly indicated for long-term invasive ventilation and similar to those of an active humidification system, as described elsewhere, 12,13 the active HME was found to share similarities and handling features with the HME.…”
Section: Discussionmentioning
confidence: 99%